Controllable Synthesis of Hollow Si Anode for Long‐Cycle‐Life Lithium‐Ion Batteries. (14th April 2014) - Huang, Xingkang; Yang, Joseph; Mao, Shun; Chang, Jingbo; Hallac, Peter B.; Fell, Christopher R.; Metz, Bernhard; Jiang, Junwei; Hurley, Patrick T.; Chen, Junhong
<x xml:space="preserve">Abstract</x> A versatile and surfactant‐free method is developed to synthesize hollow Si materials using carbonates as templates without the use of hazardous hydrofluoric acid. The morphology of Si is controllable from hollow cubes, spheres, and tubes, to flowers and other shapes. Such hollow Si materials as anodes of lithium‐ion batteries show excellent cyclic performance, which is promising for practical applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>